HUBUNGAN KERJA SAMA ANTARA ORANG TUA DAN GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA DI SMP NEGERI SATU ATAP 1 DESA BUO KECAMATAN LOLODA KABUPATEN HALMAHERA BARAT MALUKU UTARA - Taliawo, Oni; Goni, Shirley Y. V. I.; Zakarias, Jhon D. (Universitas Sam Ratulangi, 2019)
Education in the family is the first and foremost education base. A harmonious and happy family situation will give birth to a child or a good and responsible successor generation. The role parents should be as the first person in the study of the fundamentals of education on his children.In reality, most students Prefer to play, watch TV and others. The relationship that will be done between parents and teachers at SMP Negeri Satu Atap1 West Halmahera Village of Buo district of Loloda, West Halmahera regency of North Maluku, is holding a meeting or meeting to discuss increasing the students' learning interest School principals, parents and teachers related to student activities at home and at school. It is thus necessary that the relationship between parents and teachers is needed, so that students' learning interest will continue to increase so that students can excel in the future.A number of experiments and observations strengthened the fact that much of the student learned from his teacher. Students will absorb attitudes, beliefs imitating behaviors, achievements and continuous learning desires in students sourced from the personality of the teacher.Efforts made between parents and teachers in increasing the learning interest of students, parents always provide the motivation to learn to students and parents always provide learning guidance to students. Then the teacher reminded the quality of the learning by creating good learning su to make the students ' learning interest more increasing.Keywords: education, teacher, parentÂ